2019
DOI: 10.33503/journey.v2i2.535
|View full text |Cite
|
Sign up to set email alerts
|

A Sociolinguistic Analysis of Taboo Words in Alpha Dog Movie

Abstract: This study is aimed at revealing the types and functions of taboo words uttered by the characters in Alpha dog movie. This study is under the concern of sociolinguistics, which is a branch of linguistics studying language and its functions in society. It also employed a descriptive qualitative method using the researcher and a data sheet as the research instruments. The data of this study were the words, phrases, clauses, and sentences uttered by the characters of Alpha Dog movie and were collected by simak da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This section sheds light on some former studies associated with the current research. Alfarisi et al (2019) investigate a linguistic analysis to identify the categories and functions of taboo words which are uttered by the characters in the movie of Alpha Dog. This study is concerned with sociolinguistics, a branch of linguistics associated with studying language and its societal functions (Wardhaugh, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This section sheds light on some former studies associated with the current research. Alfarisi et al (2019) investigate a linguistic analysis to identify the categories and functions of taboo words which are uttered by the characters in the movie of Alpha Dog. This study is concerned with sociolinguistics, a branch of linguistics associated with studying language and its societal functions (Wardhaugh, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This word is considered very offensive to be directed to other listeners or interlocutors to show hostility or rage. Similarly, Farisi et al (2017) found that the word fuck literally means to have sexual activity that leads to a sense of disgust and becomes forbidden to be used in public media.…”
Section: Types Of Taboo Words a Obscenitymentioning
confidence: 99%
“…There are some parts of language such as words, phrase, or sentence that cannot be spoken which is called taboo words that include some subjects such as sex, death, excretion, bodily function, politics, and religious matter (Wardhaugh, 2006, p.238). Taboo words usually used when people want to show their annoyance, astonishment, hatred, etc (Alfarisi et al 2019). Hence, euphemism emerges to make words, phrases, or sentences more acceptable to society.…”
Section: Introductionmentioning
confidence: 99%